Intervención Clínica con niños, niñas y adolescentes de la Corporación Sirviendo con Amor (2011)
This report covers the academic practice held at the Casa Hogar Protection mode Corporation Serving with love, which began on January 11 and completed on November 11, 2011. The process undertaken was directed in two areas of intervention, the clinician, the therapeutic approach from individual psychoanalytic approach, and through psycho-educational workshops on risk factors and life project. These axes were identified according to the needs assessment conducted in the institution and the guidelines suggested by the Colombian Family Welfare Institute.